Посилення каральної спрямованості законодавства Української Держави доби Гетьманату Павла Скоропадського (квітень – грудень 1918 р.) - Гламазда, П.; Glamazda, P. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті висвітлено закономірності формування законодавчої бази Української Держави (квітень –грудень 1918 р.). Досліджено особливості застосовування законодавства Російської імперії в Українській Державі доби Гетьманату Павла Скоропадського, складність правотворення та причини посилення каральної спрямованості гетьманського законодавства. The article investigates the common factors in the formation of the legal framework in the Ukrainian state (April-December, 1918). The key features of the legislative execution both in the Russian Empire and in the Ukrainian state as well as the complexity of the law-making and the reasons for intensification of punitively focused legislation of the Hetman are examined. In part, on the one hand, such phenomenon took place due to the Ukrainian state leaders’ aim to approve the stability and overcome the destruction of the previous era revolutionary changes. On the other hand, such a policy is dictated by complicated political and economic situation in the country and uncertain external relations policy. According to the results of the research we can say that in a course of the investigated period a new criminal law is formed with the improved concepts and institutions to accord with the historical development. In particular the criminal law has been improved in terms of crimes against the state and criminal liability for official crimes increases.
An Intensification of Punitively Focused Legislation in Ukrainian Government Since Pavlo SkoropaDskyi Hetmanat.
Keywords: Українська Держава; гетьман Павло Скоропадський; кримінальне та кримінально- виконавче законодавство; Ukrainian State; Hetman Pavel Skoropadskyi; criminal and penal law